Tandem catalyst for preparing mixed alcohol through hydrogenation of carbon dioxide as well as preparation method and application of tandem catalyst
By using a tandem catalyst composed of a copper-based bimetallic catalyst and a zirconium-based solid solution catalyst, the existing CO2 hydrogenation and mixed alcohol catalyst have low activity and poor selectivity, and efficient CO2 conversion and C2+ alcohol selectivity are achieved, and production costs are reduced.
Patent Information
- Application Number
- CN202311199298.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-18
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-09-18
AI Technical Summary
The existing catalysts for hydrogenation of CO2 to mix alcohols have problems such as high manufacturing costs, low overall activity, harsh reaction conditions, poor selectivity of C2+ alcohols, complex products, and high selectivity of hydrocarbons.
A tandem catalyst consisting of a copper-based bimetallic catalyst and a zirconium-based solid solution catalyst is used. The expression of the copper-based bimetallic catalyst is M1-Cu-M2/SiO2 and the expression of the zirconium-based solid solution catalyst is M3-Zr. The activity and selectivity of the catalyst are improved through specific preparation methods and combination ratios.
The CO2 conversion rate reached 30%, and the selectivity of total alcohol reached about 20%, among which C2+ alcohol accounts for more than 80% of the mass fraction of the total alcohol, reducing the manufacturing cost of the catalyst and conducive to large-scale production and application.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to a series catalyst for preparing mixed alcohols by hydrogenating carbon dioxide, and a preparation method and application thereof. Background Art
[0002] Since the 19th century, humans have been exploiting fossil energy in nature on a large scale and emitting greenhouse gases such as CO2 into the environment. Excessive CO2 emissions have brought about a series of environmental problems such as the greenhouse effect and ocean acidification. Converting CO2 into various high-value-added chemicals such as alkanes, olefins, alcohols, and aromatics can not only effectively alleviate the environmental problems caused by excessive CO2 emissions, but also reduce excessive dependence on fossil energy, which is of great significance to the sustainable development of the energy and chemical industries. Alcohols can be used as fuels and fuel additives, and are also raw materials or intermediates for the production of many chemical products. The wide range of uses has led to an increasing market demand for alcohols, so the process of converting CO2 into alcohol products has received widespread attention, and the development of catalysts is the key to the CO2 hydrogenation reaction to produce alcohols.
[0003] The catalysts for CO2 hydrogenation to produce mixed alcohols are divided into four systems according to the different active components: 1. Precious metal catalysts represented by Rh group have good C 2+ 1. The modified Mo-based catalyst has good sulfur resistance, but the overall activity is low and the reaction conditions are harsh; 2. The modified methanol synthesis catalyst has high catalytic activity, but the main product is methanol; 3. The modified Fischer-Tropsch catalyst has the characteristics of low cost, high activity and mild reaction conditions, but the products are complex and the selectivity of hydrocarbons is high.
[0004] Tandem catalysis can promote the reaction through the coupling between different active components, and has been applied in many reaction systems. For tandem catalysts, the combination ratio and combination mode of active components will affect the product distribution. Therefore, how to promote carbon chain growth and improve low-carbon alcohol selectivity through efficient coupling of various parts of tandem catalysts is the key to the CO2 hydrogenation to low-carbon alcohol reaction process. Summary of the invention
[0005] One of the purposes of the present invention is to provide a tandem catalyst for preparing mixed alcohols by hydrogenation of carbon dioxide and a preparation method thereof, so as to solve the problems of the existing catalyst system for preparing mixed alcohols by hydrogenation of CO2, such as high manufacturing cost, low overall activity, harsh reaction conditions, and C 2+ Technical problems include poor alcohol selectivity, complex products, and high hydrocarbon selectivity.
[0006] The technical solution adopted by the present invention is:
[0007] A tandem catalyst for hydrogenating carbon dioxide to prepare mixed alcohols, comprising a copper-based bimetallic catalyst and a zirconium-based solid solution catalyst; the copper-based bimetallic catalyst is expressed as M1-Cu-M2 / SiO2, SiO2 is a carrier, M1, Cu, and M2 are active metals of the catalyst, M1 is one of alkali metals Na and K, and M2 is one of transition metals Co and Fe; the zirconium-based solid solution catalyst is expressed as M3-Zr, and M3 is one of Zn, Ce, and In.
[0008] Preferably, in the copper-based bimetallic catalyst, the loading amount of M1 is 1-10wt%, and the molar ratio of Cu and M2 is (0.05-20):1; in the zirconium-based solid solution catalyst, the molar ratio of M3 to Zr is (0.5-10):1.
[0009] The preparation method of the above-mentioned tandem catalyst comprises the following steps:
[0010] (3.1) Preparation of copper-based bimetallic catalysts:
[0011] (3.1.1) Soluble metal salts of Cu and M2 are dissolved in deionized water, and then SiO2 sol is added to obtain a mixed solution; aqueous ammonia is added dropwise to the mixed solution until the pH value is 10 to 11, and the solution is stirred and aged, and then the aged mixed solution is heated to evaporate ammonia to reduce the pH value of the solution to neutral to obtain a concentrated solution; the concentrated solution is filtered, washed, and dried to obtain a solid sample A; the obtained solid sample A is calcined in air to obtain Cu-M2 / SiO2;
[0012] (3.1.2) dissolving a soluble metal salt of M1 in deionized water and impregnating it onto Cu-M2 / SiO2, drying it, and calcining it in air to obtain a M1-Cu-M2 / SiO2 catalyst;
[0013] (3.2) Preparation of zirconium-based solid solution catalyst:
[0014] A soluble metal salt of Zr and a soluble metal salt of M3 are dissolved in deionized water, a precipitant is added, and the mixture is stirred and aged. The aged solution is filtered, washed, and dried to obtain a solid sample B. The obtained solid sample B is then calcined in air to obtain an M3-Zr catalyst.
[0015] (3.3) Preparation of tandem catalysts:
[0016] The M1-Cu-M2 / SiO2 catalyst prepared in step (3.1) is combined with the M3-Zr catalyst prepared in step (3.2) to obtain a tandem catalyst.
[0017] Preferably, the soluble metal salt of Cu, the soluble metal salt of M1, the soluble metal salt of M2, the soluble metal salt of Zr and the soluble metal salt of M3 are at least one of the chloride, nitrate, sulfate and acetate of the metal respectively.
[0018] Preferably, the precipitant is at least one of water-soluble carbonates, water-soluble bicarbonates and water-soluble hydroxides.
[0019] Preferably, in step (3.3), the M1-Cu-M2 / SiO2 catalyst and the M3-Zr catalyst are combined in a mass ratio of (0.5-2):1.
[0020] Preferably, in step (3.3), the catalyst combination is a mixture of M1-Cu-M2 / SiO2 catalyst and M3-Zr catalyst, or a double-bed combination.
[0021] The M1-Cu-M2 / SiO2 catalyst and the M3-Zr catalyst are particle catalysts or powder catalysts.
[0022] The second object of the present invention is to provide an application method of the above-mentioned tandem catalyst in the hydrogenation of carbon dioxide to prepare mixed alcohols.
[0023] Preferably, the application method comprises loading the series catalyst in a fixed bed reactor, introducing raw gas H2 and CO2 for hydrogenation to produce mixed alcohol, the molar ratio of H2 to CO2 being 2 to 4; the reaction temperature being 250 to 350°C; the reaction pressure being 3 to 5MPa; and the reaction space velocity being 1000 to 10000mL / (gcat·h).
[0024] Preferably, the series catalyst is tableted and granulated before loading to obtain a catalyst with a mesh size of 40 to 60.
[0025] Beneficial effects of the present invention:
[0026] (1) The Cu-based catalyst in the tandem catalyst can maintain a highly dispersed and stably coexisting M2C after reduction x -Cu 0 Active sites can directly convert CO2 into alcohols by hydrogenation; Zr-based solid solution catalysts can provide more C1 intermediates, improve the activity of the catalyst, and promote the stable progress of the reaction.
[0027] (2) The CO2 conversion rate reaches 30%, and the total alcohol selectivity reaches about 20%, among which C 2+ The mass fraction of alcohol in the total alcohol reaches more than 80%.
[0028] (3) The catalyst composition of the present invention is low in price and is conducive to large-scale production and application. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present invention more clear, the technical solution of the present invention will be clearly and completely described below in conjunction with a preferred implementation manner.
[0030] Example 1
[0031] (1) Preparation of catalyst
[0032] (1.1) 2.42 g of Cu(NO3)2·3H2O and 2.91 g of Co(NO3)2·6H2O were dissolved in 100 mL of deionized water, and then 15.42 g of 40 wt% SiO2 sol was added thereto. NH3·H2O was added dropwise to the mixed solution until the pH reached 11. The mixture was stirred and aged for 5 h. The solution was then heated to 80°C to evaporate ammonia until the pH of the solution dropped to about 7. After filtering and washing, the mixture was dried in an oven at 100°C for 12 h, and then heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain a catalyst denoted as 1Cu1Co / SiO2.
[0033] (1.2) Using the equal volume impregnation method, 0.053 g of K2CO3 was weighed and dissolved in an appropriate amount of deionized water, and then impregnated onto 1.5 g of 1Cu1Co / SiO2. After drying, the mixture was heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain 2 wt% K-1Cu1Co / SiO2.
[0034] (1.3) Take 2.98g Zn(NO3)2·6H2O and 21.47g Zr(NO3)4·5H2O and dissolve them in 150mL deionized water. Add 1mol / L (NH4)2CO3 in a water bath at 80℃ until the pH is about 9. Stir and age for 5h. After filtering and washing, dry in an oven at 100℃ for 12h. Then, heat the temperature to 500℃ in a muffle furnace at a heating rate of 5℃ / min and calcine for 5h to obtain a catalyst named 1Zn5Zr.
[0035] (1.4) Take 1g of the 2wt% K-1Cu1Co / SiO2 catalyst and 1Zn5Zr powder prepared above, mix them evenly, and then press and granulate them to obtain a 40-60 mesh granular catalyst, recorded as 2wt% K-1Cu1Co / SiO2+1Zn5Zr / (1:1).
[0036] (2) Catalyst performance evaluation
[0037] 2wt% K-1Cu1Co / SiO2+1Zn5Zr / (1:1) catalyst was loaded into the reaction tube in the constant temperature zone in the middle of the reaction tube, and the upper and lower empty parts of the reaction tube were filled with 40-60 mesh quartz sand. The catalyst was reduced with H2 before the reaction, and the reduction conditions were: temperature 320℃, flow rate 150mL·min -1 After the reduction is completed, the gas flow is switched to a mixture of H2 and CO2 with a molar ratio of 3, the system pressure is slowly increased to 5 MPa, and the temperature is lowered to 300 °C to start the reaction.
[0038] Example 2
[0039] (1) Preparation of catalyst
[0040] (1.1) 2.42 g of Cu(NO3)2·3H2O and 2.91 g of Co(NO3)2·6H2O were dissolved in 100 mL of deionized water, and then 15.42 g of 40 wt% SiO2 sol was added thereto. NH3·H2O was added dropwise to the mixed solution until the pH reached 11. The mixture was stirred and aged for 5 h. The solution was then heated to 80°C to evaporate ammonia until the pH of the solution dropped to about 7. After filtering and washing, the mixture was dried in an oven at 100°C for 12 h, and then heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain a catalyst denoted as 1Cu1Co / SiO2.
[0041] (1.2) Using the equal volume impregnation method, 0.041 g of Na2CO3 was weighed and dissolved in an appropriate amount of deionized water. The solution was then impregnated onto 1.5 g of 1Cu1Co / SiO2. After drying, the solution was heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain 2 wt% Na-1Cu1Co / SiO2.
[0042] (1.3) Take 2.98g Zn(NO3)2·6H2O and 21.47g Zr(NO3)4·5H2O and dissolve them in 150mL deionized water. Add 1mol / L (NH4)2CO3 in a water bath at 80℃ until the pH is about 9. Stir and age for 5h. After filtering and washing, dry in an oven at 100℃ for 12h. Then, heat the temperature to 500℃ in a muffle furnace at a heating rate of 5℃ / min and calcine for 5h to obtain a catalyst named 1Zn5Zr.
[0043] (1.4) Take 1g of the 2wt% Na-1Cu1Co / SiO2 catalyst and 1Zn5Zr powder prepared above, mix them evenly, and then press and granulate them to obtain a 40-60 mesh granular catalyst, recorded as 2wt% Na-1Cu1Co / SiO2+1Zn5Zr / (1:1).
[0044] (2) Catalyst performance evaluation
[0045] 2wt% Na-1Cu1Co / SiO2+1Zn5Zr / (1:1) catalyst was loaded into the reaction tube in the constant temperature zone in the middle of the reaction tube, and the upper and lower empty parts of the reaction tube were filled with 40-60 mesh quartz sand. The reduction and reaction conditions were the same as in Example 1.
[0046] Example 3
[0047] (1) Preparation of catalyst
[0048] (1.1) 2.42 g of Cu(NO3)2·3H2O and 4.04 g of Fe(NO3)2·9H2O were dissolved in 100 mL of deionized water, and then 15.95 g of 40 wt% SiO2 sol was added thereto. NH3·H2O was added dropwise to the mixed solution until the pH value reached 11. The mixture was stirred and aged for 5 h. The solution was then heated to 80°C to evaporate ammonia until the pH value of the solution dropped to about 7. After filtering and washing, the mixture was dried in an oven at 100°C for 12 h, and then heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain a catalyst denoted as 1Cu1Fe / SiO2.
[0049] (1.2) Using the equal volume impregnation method, 0.053 g of K2CO3 was weighed and dissolved in an appropriate amount of deionized water, and then impregnated onto 1.5 g of 1Cu1Fe / SiO2. After drying, the mixture was heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain 2 wt% K-1Cu1Fe / SiO2.
[0050] (1.3) Take 2.98g Zn(NO3)2·6H2O and 21.47g Zr(NO3)4·5H2O and dissolve them in 150mL deionized water. Add 1mol / L (NH4)2CO3 in a water bath at 80℃ until the pH is about 9. Stir and age for 5h. After filtering and washing, dry in an oven at 100℃ for 12h. Then, heat the temperature to 500℃ in a muffle furnace at a heating rate of 5℃ / min and calcine for 5h to obtain a catalyst named 1Zn5Zr.
[0051] (1.4) Take 1g of the 2wt% K-1Cu1Fe / SiO2 catalyst and 1Zn5Zr catalyst powder prepared above, mix them evenly, and then press and granulate them to obtain a 40-60 mesh granular catalyst, recorded as 2wt% K-1Cu1Fe / SiO2+1Zn5Zr / (1:1).
[0052] (2) Catalyst performance evaluation
[0053] 2wt% K-1Cu1Fe / SiO2+1Zn5Zr / (1:1) catalyst was loaded into the constant temperature zone in the middle of the reaction tube, and the upper and lower empty parts of the reaction tube were filled with 40-60 mesh quartz sand. The reduction and reaction conditions were the same as those in Example 1.
[0054] Example 4
[0055] (1) Preparation of catalyst
[0056] (1.1) 4.84 g of Cu(NO3)2·3H2O and 2.91 g of Co(NO3)2·6H2O were dissolved in 100 mL of deionized water, and then 23.39 g of 40 wt% SiO2 sol was added thereto. NH3·H2O was added dropwise to the mixed solution until the pH reached 11. The mixture was stirred and aged for 5 h. The solution was then heated to 80°C to evaporate ammonia until the pH of the solution dropped to about 7. After filtering and washing, the mixture was dried in an oven at 100°C for 12 h, and then heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain a catalyst named 2Cu1Co / SiO2.
[0057] (1.2) Using the equal volume impregnation method, 0.053 g of K2CO3 was weighed and dissolved in an appropriate amount of deionized water, and then impregnated onto 1.5 g of 2Cu1Co / SiO2. After drying, the mixture was heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain 2 wt% K-2Cu1Co / SiO2.
[0058] (1.3) Take 2.98g Zn(NO3)2·6H2O and 21.47g Zr(NO3)4·5H2O and dissolve them in 150mL deionized water. Add 1mol / L (NH4)2CO3 in a water bath at 80℃ until the pH is about 9. Stir and age for 5h. After filtering and washing, dry in an oven at 100℃ for 12h. Then, heat the temperature to 500℃ in a muffle furnace at a heating rate of 5℃ / min and calcine for 5h to obtain a catalyst named 1Zn5Zr.
[0059] (1.4) Take 1g of the 2wt% K-2Cu1Co / SiO2 catalyst and 1Zn5Zr catalyst powder prepared above, mix them evenly, and then press and granulate them to obtain a 40-60 mesh granular catalyst, recorded as 2wt% K-2Cu1Co / SiO2+1Zn5Zr / (1:1).
[0060] (2) Catalyst performance evaluation
[0061] 2wt% K-2Cu1Co / SiO2+1Zn5Zr / (1:1) catalyst was loaded into the constant temperature zone in the middle of the reaction tube, and the upper and lower empty parts of the reaction tube were filled with 40-60 mesh quartz sand. The reduction and reaction conditions were the same as those in Example 1.
[0062] Example 5
[0063] (1) Preparation of catalyst
[0064] (1.1) 2.42 g of Cu(NO3)2·3H2O and 5.82 g of Co(NO3)2·6H2O were dissolved in 100 mL of deionized water, and then 22.94 g of 40 wt% SiO2 sol was added thereto. NH3·H2O was added dropwise to the mixed solution until the pH reached 11. The mixture was stirred and aged for 5 h. The solution was then heated to 80°C to evaporate ammonia until the pH of the solution dropped to about 7. After filtering and washing, the mixture was dried in an oven at 100°C for 12 h, and then heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain a catalyst denoted as 1Cu2Co / SiO2.
[0065] (1.2) Using the equal volume impregnation method, 0.053 g of K2CO3 was weighed and dissolved in an appropriate amount of deionized water, and then impregnated onto 1.5 g of 1Cu2Co / SiO2. After drying, the mixture was heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain 2 wt% K-1Cu2Co / SiO2.
[0066] (1.3) Take 2.98g Zn(NO3)2·6H2O and 21.47g Zr(NO3)4·5H2O and dissolve them in 150mL deionized water. Add 1mol / L (NH4)2CO3 in a water bath at 80℃ until the pH is about 9. Stir and age for 5h. After filtering and washing, dry in an oven at 100℃ for 12h. Then, heat the temperature to 500℃ in a muffle furnace at a heating rate of 5℃ / min and calcine for 5h to obtain a catalyst named 1Zn5Zr.
[0067] (1.4) Take 1g of the 2wt% K-1Cu2Co / SiO2 catalyst and 1Zn5Zr catalyst powder prepared above, mix them evenly, and then press and granulate them to obtain a 40-60 mesh granular catalyst, recorded as 2wt% K-1Cu2Co / SiO2+1Zn5Zr / (1:1).
[0068] (2) Catalyst performance evaluation
[0069] 2wt% K-1Cu2Co / SiO2+1Zn5Zr / (1:1) catalyst was loaded into the constant temperature zone in the middle of the reaction tube, and the upper and lower empty parts of the reaction tube were filled with 40-60 mesh quartz sand. The reduction and reaction conditions were the same as those in Example 1.
[0070] Example 6
[0071] (1) Preparation of catalyst
[0072] (1.1) 2.42 g of Cu(NO3)2·3H2O and 2.91 g of Co(NO3)2·6H2O were dissolved in 100 mL of deionized water, and then 22.94 g of 40 wt% SiO2 sol was added thereto. NH3·H2O was added dropwise to the mixed solution until the pH value reached 11. The mixture was stirred and aged for 5 h. The solution was then heated to 80°C to evaporate ammonia until the pH value of the solution dropped to about 7. After filtration and washing, the mixture was dried in an oven at 100°C for 12 h, and then heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain a catalyst denoted as 1Cu1Co / SiO2.
[0073] (1.2) Using the equal volume impregnation method, 0.053 g of K2CO3 was weighed and dissolved in an appropriate amount of deionized water, and then impregnated onto 1.5 g of 1Cu1Co / SiO2. After drying, the mixture was heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain 2 wt% K-1Cu1Co / SiO2.
[0074] (1.3) Take 2.98g Zn(NO3)2·6H2O and 21.47g Zr(NO3)4·5H2O and dissolve them in 150mL deionized water. Add 1mol / L (NH4)2CO3 in a water bath at 80℃ until the pH is about 9. Stir and age for 5h. After filtering and washing, dry in an oven at 100℃ for 12h. Then, heat the temperature to 500℃ in a muffle furnace at a heating rate of 5℃ / min and calcine for 5h to obtain a catalyst named 1Zn5Zr.
[0075] (1.4) Take 1g of the 2wt%-1Cu1Co / SiO2 catalyst and 1Zn5Zr catalyst prepared above, and press and granulate them to obtain 40-60 mesh granular catalysts.
[0076] (2) Catalyst performance evaluation
[0077] 2wt% K-1Cu1Co / SiO2 catalyst and 1Zn5Zr catalyst were respectively loaded in the constant temperature zone of the reaction tube, 2wt% K-1Cu1Co / SiO2 was on the top, 1Zn5Zr was on the bottom, separated by about 1cm thick quartz sand in the middle, and the remaining part of the reaction tube was filled with 40-60 mesh quartz sand. The reduction and reaction conditions were the same as in Example 1.
[0078] Example 7
[0079] (1) Preparation of catalyst
[0080] (1.1) 2.42 g of Cu(NO3)2·3H2O and 2.91 g of Co(NO3)2·6H2O were dissolved in 100 mL of deionized water, and then 22.94 g of 40 wt% SiO2 sol was added thereto. NH3·H2O was added dropwise to the mixed solution until the pH value reached 11. The mixture was stirred and aged for 5 h. The solution was then heated to 80°C to evaporate ammonia until the pH value of the solution dropped to about 7. After filtration and washing, the mixture was dried in an oven at 100°C for 12 h, and then heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain a catalyst denoted as 1Cu1Co / SiO2.
[0081] (1.2) Using the equal volume impregnation method, 0.053 g of K2CO3 was weighed and dissolved in an appropriate amount of deionized water, and then impregnated onto 1.5 g of 1Cu1Co / SiO2. After drying, the mixture was heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain 2 wt% K-1Cu1Co / SiO2.
[0082] (1.3) Take 2.98g Zn(NO3)2·6H2O and 21.47g Zr(NO3)4·5H2O and dissolve them in 150mL deionized water. Add 1mol / L (NH4)2CO3 in a water bath at 80℃ until the pH is about 9. Stir and age for 5h. After filtering and washing, dry in an oven at 100℃ for 12h. Then, heat the temperature to 500℃ in a muffle furnace at a heating rate of 5℃ / min and calcine for 5h to obtain a catalyst named 1Zn5Zr.
[0083] (1.4) Take 1g of the 2wt% K-1Cu1Co / SiO2 catalyst and 1Zn5Zr catalyst prepared above, and press and granulate them to obtain 40-60 mesh granular catalysts.
[0084] (2) Catalyst performance evaluation
[0085] 2wt% K-1Cu1Co / SiO2 catalyst and 1Zn5Zr catalyst were respectively loaded in the constant temperature zone of the reaction tube, 1Zn5Zr was on the top, 2wt% K-1Cu1Co / SiO2 was on the bottom, separated by about 1cm thick quartz sand in the middle, and the remaining part of the reaction tube was filled with 40-60 mesh quartz sand. The reduction and reaction conditions were the same as in Example 1.
[0086] Example 8
[0087] (1) Preparation of catalyst
[0088] (1.1) 2.42 g of Cu(NO3)2·3H2O and 2.91 g of Co(NO3)2·6H2O were dissolved in 100 mL of deionized water, and then 22.94 g of 40 wt% SiO2 sol was added thereto. NH3·H2O was added dropwise to the mixed solution until the pH value reached 11. The mixture was stirred and aged for 5 h. The solution was then heated to 80°C to evaporate ammonia until the pH value of the solution dropped to about 7. After filtration and washing, the mixture was dried in an oven at 100°C for 12 h, and then heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain a catalyst denoted as 1Cu1Co / SiO2.
[0089] (1.2) Using the equal volume impregnation method, 0.053 g of K2CO3 was weighed and dissolved in an appropriate amount of deionized water, and then impregnated onto 1.5 g of 1Cu1Co / SiO2. After drying, the mixture was heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain 2 wt% K-1Cu1Co / SiO2.
[0090] (1.3) Take 2.98g Zn(NO3)2·6H2O and 21.47g Zr(NO3)4·5H2O and dissolve them in 150mL deionized water. Add 1mol / L (NH4)2CO3 in a water bath at 80℃ until the pH is about 9. Stir and age for 5h. After filtering and washing, dry in an oven at 100℃ for 12h. Then, heat the temperature to 500℃ in a muffle furnace at a heating rate of 5℃ / min and calcine for 5h to obtain a catalyst named 1Zn5Zr.
[0091] (1.4) Take 1g of each of the 2wt% K-1Cu1Co / SiO2 catalyst and 1Zn5Zr catalyst prepared above, and perform tableting and granulation to obtain particles of 40-60 mesh. Mix the two catalyst particles evenly to obtain a mixed catalyst, recorded as 2wt% K-1Cu1Co / SiO2 particles + 1Zn5Zr particles / (1:1).
[0092] (2) Catalyst performance evaluation
[0093] 2wt% K-1Cu1Co / SiO2 particles + 1Zn5Zr particles / (1:1) catalyst was filled in the constant temperature zone in the middle of the reaction tube, and the upper and lower empty parts of the reaction tube were filled with 40-60 mesh quartz sand. The reduction and reaction conditions were the same as in Example 1.
[0094] Example 9
[0095] (1) Preparation of catalyst
[0096] (1.1) 2.42 g of Cu(NO3)2·3H2O and 2.91 g of Co(NO3)2·6H2O were dissolved in 100 mL of deionized water, and then 15.42 g of 40 wt% SiO2 sol was added thereto. NH3·H2O was added dropwise to the mixed solution until the pH reached 11. The mixture was stirred and aged for 5 h. The solution was then heated to 80°C to evaporate ammonia until the pH of the solution dropped to about 7. After filtration and washing, the mixture was dried in an oven at 100°C for 12 h, and then heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain a catalyst denoted as 1Cu1Co / SiO2.
[0097] (1.2) Using the equal volume impregnation method, 0.053 g of K2CO3 was weighed and dissolved in an appropriate amount of deionized water, and then impregnated onto 1.5 g of 1Cu1Co / SiO2. After drying, the mixture was heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain 2 wt% K-1Cu1Co / SiO2.
[0098] (1.3) Take 2.98g Zn(NO3)2·6H2O and 21.47g Zr(NO3)4·5H2O and dissolve them in 150mL deionized water. Add 1mol / L (NH4)2CO3 in a water bath at 80℃ until the pH is about 9. Stir and age for 5h. After filtering and washing, dry in an oven at 100℃ for 12h. Then, heat the temperature to 500℃ in a muffle furnace at a heating rate of 5℃ / min and calcine for 5h to obtain a catalyst named 1Zn5Zr.
[0099] (1.4) Take 2g of the 2wt% K-1Cu1Co / SiO2 catalyst prepared above and 1g of 1Zn5Zr powder, mix them evenly, and then press and granulate them to obtain a 40-60 mesh granular catalyst, recorded as 2wt% K-1Cu1Co / SiO2+1Zn5Zr / (2:1).
[0100] (2) Catalyst performance evaluation
[0101] 2wt% K-1Cu1Co / SiO2+1Zn5Zr (2:1) catalyst was loaded into the reaction tube in the constant temperature zone in the middle of the reaction tube, and the upper and lower empty parts of the reaction tube were filled with 40-60 mesh quartz sand. The reduction and reaction conditions were the same as those in Example 1.
[0102] Example 10
[0103] (1) Preparation of catalyst
[0104] (1.1) 2.42 g of Cu(NO3)2·3H2O and 2.91 g of Co(NO3)2·6H2O were dissolved in 100 mL of deionized water, and then 15.42 g of 40 wt% SiO2 sol was added thereto. NH3·H2O was added dropwise to the mixed solution until the pH reached 11. The mixture was stirred and aged for 5 h. The solution was then heated to 80°C to evaporate ammonia until the pH of the solution dropped to about 7. After filtration and washing, the mixture was dried in an oven at 100°C for 12 h, and then heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain a catalyst denoted as 1Cu1Co / SiO2.
[0105] (1.2) Using the equal volume impregnation method, 0.053 g of K2CO3 was weighed and dissolved in an appropriate amount of deionized water, and then impregnated onto 1.5 g of 1Cu1Co / SiO2. After drying, the mixture was heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain 2 wt% K-1Cu1Co / SiO2.
[0106] (1.3) Take 2.98g Zn(NO3)2·6H2O and 21.47g Zr(NO3)4·5H2O and dissolve them in 150mL deionized water. Add 1mol / L (NH4)2CO3 in a water bath at 80℃ until the pH is about 9. Stir and age for 5h. After filtering and washing, dry in an oven at 100℃ for 12h. Then, heat the temperature to 500℃ in a muffle furnace at a heating rate of 5℃ / min and calcine for 5h to obtain a catalyst named 1Zn5Zr.
[0107] (1.4) Take 1g of the 2wt% K-1Cu1Co / SiO2 catalyst prepared above and 2g of 1Zn5Zr powder, mix them evenly, and then press and granulate them to obtain a 40-60 mesh granular catalyst, recorded as 2wt% K-1Cu1Co / SiO2+1Zn5Zr / (1:2).
[0108] (2) Catalyst performance evaluation
[0109] 2wt% K-1Cu1Co / SiO2+1Zn5Zr / (1:2) catalyst was loaded into the reaction tube in the constant temperature zone in the middle of the reaction tube, and the upper and lower empty parts of the reaction tube were filled with 40-60 mesh quartz sand. The reduction and reaction conditions were the same as in Example 1.
[0110] Embodiment 11
[0111] (1) Preparation of catalyst
[0112] (1.1) 2.42 g of Cu(NO3)2·3H2O and 2.91 g of Co(NO3)2·6H2O were dissolved in 100 mL of deionized water, and then 15.42 g of 40 wt% SiO2 sol was added thereto. NH3·H2O was added dropwise to the mixed solution until the pH reached 11. The mixture was stirred and aged for 5 h. The solution was then heated to 80°C to evaporate ammonia until the pH of the solution dropped to about 7. After filtering and washing, the mixture was dried in an oven at 100°C for 12 h, and then heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain a catalyst denoted as 1Cu1Co / SiO2.
[0113] (1.2) Using the equal volume impregnation method, 0.053 g of K2CO3 was weighed and dissolved in an appropriate amount of deionized water, and then impregnated onto 1.5 g of 1Cu1Co / SiO2. After drying, the mixture was heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain 2 wt% K-1Cu1Co / SiO2.
[0114] (1.3) Take 3.01g In(NO3)3·xH2O and 21.47g Zr(NO3)4·5H2O and dissolve them in 150mL deionized water. Add 1mol / L (NH4)2CO3 in a water bath at 80℃ until the pH is about 9. Stir and age for 5h. After filtering and washing, dry in an oven at 100℃ for 12h. Then, heat the temperature to 500℃ in a muffle furnace at a heating rate of 5℃ / min and calcine for 5h to obtain a catalyst named 1In5Zr.
[0115] (1.4) Take 1g of the 2wt% K-1Cu1Co / SiO2 catalyst and 1In5Zr powder prepared above, mix them evenly, and then press and granulate them to obtain a 40-60 mesh granular catalyst, recorded as 2wt% K-1Cu1Co / SiO2+1In5Zr / (1:1).
[0116] (2) Catalyst performance evaluation
[0117] 2wt% K-1Cu1Co / SiO2+1In5Zr / (1:1) catalyst was loaded into the reaction tube in the constant temperature zone in the middle of the reaction tube, and the upper and lower empty parts of the reaction tube were filled with 40-60 mesh quartz sand. The reduction and reaction conditions were the same as those in Example 1.
[0118] Example 12
[0119] (1) Preparation of catalyst
[0120] (1.1) 2.42 g of Cu(NO3)2·3H2O and 2.91 g of Co(NO3)2·6H2O were dissolved in 100 mL of deionized water, and then 15.42 g of 40 wt% SiO2 sol was added thereto. NH3·H2O was added dropwise to the mixed solution until the pH reached 11. The mixture was stirred and aged for 5 h. The solution was then heated to 80°C to evaporate ammonia until the pH of the solution dropped to about 7. After filtering and washing, the mixture was dried in an oven at 100°C for 12 h, and then heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain a catalyst denoted as 1Cu1Co / SiO2.
[0121] (1.2) Using the equal volume impregnation method, 0.053 g of K2CO3 was weighed and dissolved in an appropriate amount of deionized water, and then impregnated onto 1.5 g of 1Cu1Co / SiO2. After drying, the mixture was heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain 2 wt% K-1Cu1Co / SiO2.
[0122] (1.3) Take 4.34g Ce(NO3)3·6H2O and 21.47g Zr(NO3)4·5H2O and dissolve them in 150mL deionized water. Add 1mol / L (NH4)2CO3 in a water bath at 80℃ until the pH is about 9. Stir and age for 5h. After filtering and washing, dry in an oven at 100℃ for 12h. Then, heat to 500℃ in a muffle furnace at a heating rate of 5℃ / min and calcine for 5h to obtain a catalyst named 1Ce5Zr.
[0123] (1.4) Take 1g of the 2wt% K-1Cu1Co / SiO2 catalyst and 1Ce5Zr powder prepared above, mix them evenly, and then press and granulate them to obtain a 40-60 mesh granular catalyst, recorded as 2wt% K-1Cu1Co / SiO2+1Ce5Zr / (1:1).
[0124] (2) Catalyst performance evaluation
[0125] 2wt% K-1Cu1Co / SiO2+1Ce5Zr / (1:1) catalyst was loaded into the reaction tube in the constant temperature zone in the middle of the reaction tube, and the upper and lower empty parts of the reaction tube were filled with 40-60 mesh quartz sand. The reduction and reaction conditions were the same as those in Example 1. Comparative Example 1
[0126] (1) Preparation of catalyst
[0127] (1.1) 2.42 g of Cu(NO3)2·3H2O and 2.91 g of Co(NO3)2·6H2O were dissolved in 100 mL of deionized water, and then 22.94 g of 40 wt% SiO2 sol was added thereto. NH3·H2O was added dropwise to the mixed solution until the pH value reached 11. The mixture was stirred and aged for 5 h. The solution was then heated to 80°C to evaporate ammonia until the pH value of the solution dropped to about 7. After filtration and washing, the mixture was dried in an oven at 100°C for 12 h, and then heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain a catalyst denoted as 1Cu1Co / SiO2.
[0128] (1.2) Using the equal volume impregnation method, 0.053 g of K2CO3 was weighed and dissolved in an appropriate amount of deionized water. The mixture was impregnated onto 1.5 g of 1Cu1Co / SiO2. After drying, the mixture was heated to 500°C in a muffle furnace at a heating rate of 5°C / min and calcined for 5 h to obtain 2 wt% K-1Cu1Co / SiO2.
[0129] (1.32) Take 1g of the 2wt% K-1Cu1Co / SiO2 catalyst prepared above and press it into tablets and granulate it to obtain a 40-60 mesh granular catalyst.
[0130] (2) Catalyst performance evaluation
[0131] 2 wt% K-1Cu1Co / SiO2 catalyst was filled in the constant temperature zone in the middle of the reaction tube, and the upper and lower empty parts of the reaction tube were filled with 40-60 mesh quartz sand. The reduction and reaction conditions were the same as those in Example 1.
[0132] Comparative Example 2
[0133] (1) Preparation of catalyst
[0134] (1.1) Take 2.98g Zn(NO3)2·6H2O and 21.47g Zr(NO3)4·5H2O and dissolve them in 150mL deionized water. Add 1mol / L (NH4)2CO3 in a water bath at 80℃ until the pH is about 9. Stir and age for 5h. After filtering and washing, dry in an oven at 100℃ for 12h. Then, heat to 500℃ in a muffle furnace at a heating rate of 5℃ / min and calcine for 5h to obtain a catalyst named 1Zn5Zr.
[0135] (1.2) Take 1g of the 1Zn5Zr catalyst prepared above and press it into tablets and granulate it to obtain a 40-60 mesh granular catalyst.
[0136] (2) Catalyst performance evaluation
[0137] The 1Zn5Zr catalyst was filled in the constant temperature zone in the middle of the reaction tube, and the free space above and below the reaction tube was filled with quartz sand of 40-60 mesh. The reduction and reaction conditions were the same as those in Example 1.
[0138] Table 1 Catalyst performance test results
[0139]
[0140]
[0141] It can be seen from Table 1 that compared with the single copper-based bimetallic catalyst or zirconium-based solid solution catalyst (Comparative Examples 1-2), the tandem catalysts prepared in the present invention (Examples 1-12) can effectively improve the CO2 conversion rate and C 2+ In addition, when the powder mixture was used and the mass ratio of copper-based catalyst to zirconium-based solid solution catalyst was 1:1, the CO2 conversion rate was 37.5%, and the C 2+ The selectivity of alcohol is 20.1%, C 2+ The technical effect is that the proportion of alcohol to total alcohol is as high as 92.5%.
[0142] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications are also within the protection scope of the present invention.
Claims
1. A tandem catalyst for hydrogenating carbon dioxide to prepare mixed alcohols, characterized in that: It is composed of a copper-based bimetallic catalyst and a zirconium-based solid solution catalyst; the expression of the copper-based bimetallic catalyst is M1-Cu-M2 / SiO2, SiO2 is a carrier, M1, Cu, M2 are active metals of the catalyst, M1 is one of the alkali metals Na and K, and M2 is one of the transition metals Co and Fe; the expression of the zirconium-based solid solution catalyst is M3-Zr, and M3 is one of Zn, Ce, and In.
2. The tandem catalyst according to claim 1, characterized in that In the copper-based bimetallic catalyst, the loading amount of M1 is 1-10wt%, and the molar ratio of Cu to M2 is (0.05-20):1; in the zirconium-based solid solution catalyst, the molar ratio of M3 to Zr is (0.5-10):
1.
3. The method for preparing the tandem catalyst according to claim 1 or 2, characterized in that: The following steps are involved: (3.1) Preparation of copper-based bimetallic catalysts: (3.1.1) Soluble metal salts of Cu and M2 are dissolved in deionized water, and then SiO2 sol is added to obtain a mixed solution; aqueous ammonia is added dropwise to the mixed solution until the pH value is 10 to 11, and the solution is stirred and aged, and then the aged mixed solution is heated to evaporate ammonia to reduce the pH value of the solution to neutral to obtain a concentrated solution; the concentrated solution is filtered, washed, and dried to obtain a solid sample A; The obtained solid sample A was calcined in air to obtain Cu-M2 / SiO2; (3.1.2) dissolving a soluble metal salt of M1 in deionized water and impregnating it onto Cu-M2 / SiO2, drying it, and calcining it in air to obtain a M1-Cu-M2 / SiO2 catalyst; (3.2) Preparation of zirconium-based solid solution catalyst: A soluble metal salt of Zr and a soluble metal salt of M3 are dissolved in deionized water, a precipitant is added, and the mixture is stirred and aged. The aged solution is filtered, washed, and dried to obtain a solid sample B. The obtained solid sample B is then calcined in air to obtain an M3-Zr catalyst. (3.3) Preparation of tandem catalysts: The M1-Cu-M2 / SiO2 catalyst prepared in step (3.1) is combined with the M3-Zr catalyst prepared in step (3.2) to obtain a tandem catalyst.
4. The preparation method according to claim 3, characterized in that: The soluble metal salt of Cu, the soluble metal salt of M1, the soluble metal salt of M2, the soluble metal salt of Zr, and the soluble metal salt of M3 are at least one of chlorides, nitrates, sulfates, and acetates of the metals, respectively.
5. The preparation method according to claim 3, characterized in that: The precipitant is at least one of water-soluble carbonates, water-soluble bicarbonates, and water-soluble hydroxides.
6. The preparation method according to claim 3, characterized in that: In step (3.3), the M1-Cu-M2 / SiO2 catalyst and the M3-Zr catalyst are combined in a mass ratio of (0.5-2):
1.
7. The preparation method according to claim 3, characterized in that: In step (3.3), the catalyst combination is a mixture of M1-Cu-M2 / SiO2 catalyst and M3-Zr catalyst, or a double-bed combination.
8. Use of the tandem catalyst according to claim 1 in preparing mixed alcohols by hydrogenation of carbon dioxide.
9. The application method according to claim 8, characterized in that: The method comprises loading the series catalyst in a fixed bed reactor, introducing raw gas H2 and CO2 to carry out hydrogenation to prepare mixed alcohol, wherein the molar ratio of H2 to CO2 is 2-4; the reaction temperature is 250-350°C; the reaction pressure is 3-5MPa; and the reaction space velocity is 1000-10000mL / (gcat·h).
10. The application method according to claim 9, characterized in that: The series catalyst is tableted and granulated before loading to obtain a catalyst with a mesh size of 40 to 60.
Citation Information
Patent Citations
Catalyst for synthesizing methanol by hydrogenating carbon dioxide, preparation method and application thereof
CN101757943A
Catalyst for preparing low-carbon alcohol from biomass synthesis gas and preparation method of catalyst
CN104148078A
Iron-based catalyst used for Fischer-Tropsch synthesis, preparation method and application
CN104815659A
Method of improving reaction performance in preparation of higher alcohols (C<6+> alcohol) through synthetic gas one-step method by means of bifunctional catalyst combination system
CN106362795A
Tandem catalyst for preparing aromatic hydrocarbon through direct hydrogenation of carbon dioxide as well as preparation method and application of tandem catalyst
CN115155588A